Polarized Light and Polarization Vision in Animal Sciences 2014
DOI: 10.1007/978-3-642-54718-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of the Sky

Abstract: International audienceBased on full-sky imaging polarimetric measurements, in this chapter we demonstrate that the celestial distribution of the angle of polarization (or E-vector direction) of skylight is a very robust pattern being qualitatively always the same under all possible sky conditions. Practically the only qualitative difference among clear, partly cloudy, overcast, foggy, smoky and tree-canopied skies occurs in the degree of linear polarization d: The higher the optical thickness of the non-clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…We found that gibbous moon skylight (93–98% fullness; Fig. 2 A–B) measured in rural South Africa reached degrees of polarization as high as 0.6–0.7, similar to values reported for sunlit skies (Berry et al ., 2004; Horváth et al ., 2014) but much greater than the levels, around 0.27, for lunar skylight measured in Europe (Supplement S2.1 A; 80% illuminated). We also found that the maximum degree of polarization for other lunar phases was lower, with degree of polarization corresponding to moon fullness (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that gibbous moon skylight (93–98% fullness; Fig. 2 A–B) measured in rural South Africa reached degrees of polarization as high as 0.6–0.7, similar to values reported for sunlit skies (Berry et al ., 2004; Horváth et al ., 2014) but much greater than the levels, around 0.27, for lunar skylight measured in Europe (Supplement S2.1 A; 80% illuminated). We also found that the maximum degree of polarization for other lunar phases was lower, with degree of polarization corresponding to moon fullness (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On all moonlit nights the highest degree of polarization was measured in a band at approximately 90° from the moon (Fig. 2), mimicking that of the sunlit sky (Berry et al ., 2004; Horváth et al ., 2014), as found for previous studies of the polarization of lunar skylight (Gál et al ., 2001; Kyba et al ., 2011; Barta et al ., 2014; Tang et al ., 2016). Although the serial-imaging protocol we employed can lead to the accumulation of motion artefacts, particularly during long exposures, these effects appeared to be limited, for the most part, to a small number of bright stars (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The celestial distribution of the angle of the skylight polarization, being the same under all possible sky conditions (clear, fog, clouds, etc), is used for the orientation by polarization-sensitive animals, including many vertebrates [3](Horváth et al, 2014). There is considerable behavioral and physiological evidence for polarization-based navigation in vertebrates, including fish, reptiles and birds, but not in mammals, while it is known that mammals, including humans, can still perceive the polarization of light to some extent (Muheim, 2011; Wehner, 2014) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…around sunset and sunrise when large portions of the sky are red and orange, or when the sky is covered by grey or white clouds or fog. However, in the latter cases the d of skylight can be so low [811] that it falls below the perception threshold d * of Haidinger's brushes. The brushes have the best contrast when d approaches 100%, for instance looking at a white area on a liquid crystal computer monitor, which employs a linear polarizer as part of the image-forming technology [2,12].…”
Section: Introductionmentioning
confidence: 99%